Student’s Self-Confidence Restoration with Peer Mentoring Strategy - Blegur, Jusuf; Wasak, M. Rambu P.; Rosari, Renya (European Scientific Journal, ESJ, 2019)
The research objective is to restore students’ self-confidence in learning process using peer mentoring strategies. The research design used is classroom action research by involving students who experience selfconfidence problems determined purposively (five participants). Data were collected using participant observation, in-depth interviews, and field notes. Data were analyzed quantitatively (frequence and percentage) and qualitatively using Creswell’s model with seven segments of analysis, ranging from the process of collecting data to interpreting themes. The results prove that the efforts to restore students’ self-confidence succeed in five strategies, including three initial strategies (cycle 1), forming limited and intimate group discussion, placing peers who inherit caring, supportive, and inspiring, attitude and providing clear or detailed assignments. While the next two strategies (cycle 2) are to give full trust to students to execute their duties in form of performance and to conduct evaluations based on improvement using students advantages. Consequently, the increase from the first cycle to the second cycle for each participant are P1 = 18.75%, P2 = 17.1875%, P3 = 23.4375%, P4 = 17.1875%, and P5 = 20.3125%. Peer mentoring is very helpful for educators to share roles in an effort to improve student learning performance, for instance improving self-confidence. In addition, peer mentoring can be used by educators to improve the quality of learning in other aspects such as learning outcomes, social intelligence, transformational leadership, and so forth.